Reflexión sobre la percepción de universitarios en las metodologías evaluativas desde la formación e impacto en su desarrollo integral como un futuro profesional - Cindy Karina Leal Ortega; Erika Alejandra Maldonado Estévez; Yocimar Reyes Torrado; Jhon Franklin Espinosa Castro (Mundo Fesc)
The conception and practice of assessment has been expressed in different discourses, pedagogical practices, and scientific studies. It also faces current challenges, such as advanced technologies and the innovation of digital learning resources, which require updated proposals, which are little known, and if known, are rarely practiced. This article presents a reflection on some methodological processes implemented in assessment, within the uniqueness of training in Higher Education contexts. The objective is to analyze the planning behind assessment processes and how these permeate professionals. In turn, whether these respond to current challenges and requirements from the technological, scientific, and social spheres. In view of this, their importance lies in how assessment methodologies impact curricula and forge comprehensive practices oriented toward subjects in training. The sample consisted of 295 students from Simón Bolívar University (Cúcuta campus) and Francisco de Paula Santander University, through a perception survey administered via an online form. Highlighting the importance of analyzing the evaluation system in student training, because evaluation processes have become a transfer of information or memorization processes.